Changes in prey fields increase the potential for spatial overlap between gentoo penguins and a krill fishery within a marine protected area. Issue 3 (12th January 2021) - Ratcliffe, Norman; Deagle, Bruce; Love, Kieran; Polanowski, Andrea; Fielding, Sophie; Wood, Andrew G.; Hill, Simeon; Grant, Susie; Belchier, Mark; Fleming, Andrew; Hall, Jonathan
Abstract: AIM: Management of competition with predators is an important consideration for fisheries, particularly within marine protected areas (MPAs) where conservation is a primary objective. We aimed to test whether static no‐take zones within a large, sustainable‐use MPA prevented overlap between gentoo penguins and a krill fishery during two winters with contrasting prey fields. LOCATION: South Georgia, Southwest Atlantic Ocean. METHOD: We used satellite tracking ( N  = 16, June–September 2018) to describe gentoo penguin movements and distribution and quantified their overlap with the MPA's no‐take zone (NTZ) and the krill fishing grounds. DNA metabarcoding of scats ( N  = 220, April–September 2018) was used to quantify diet. RESULTS: When krill were at moderate densities and evenly distributed in 2001, gentoo penguins would have spent all of their time within the 12 NM NTZ, but when availability was low in 2018, they spent 46.3% of their time outside the NTZ and 9.6% within the krill fishing grounds. The extension of the NTZ to 30 km in response to this finding would have produced a 14.9% increase in protection for penguins and displaced 4% of fishery hauls. Gentoo penguin diet comprised 25.8% krill, which is lower than in the late 1980s but more than in 2009. MAIN CONCLUSIONS: Gentoo penguins extend their foraging range when krill is scarce, which increases the potential for spatial overlap with the krill fishery during periods of nutritional stress. Current regulations allow for expansion of both extent and catches by the krill fishery and, should this occur, gentoo penguins may face heightened risks from competition. A dynamic ocean management framework, that extends closed areas in response to near real‐time data on penguin movements and krill density estimates, may reduce the potential for competition in this sustainable‐use MPA while allowing a profitable krill fishery.